DETERMINAN STRUKTUR MODAL DAN DAMPAKNYA TERHADAP NILAI PERUSAHAAN - Handayani, Maria Eki; Ichwanudin, Wawan; Khaerunnisa, Enis (ANALISIS, 2023)
This study tested the determinants of capital structure and its impact on the value of the company. The determinant variables of Capital Structure used are Profitability, Liquidity and Asset Structure. This study uses data from the IDX using a sample of companies that are members of the IDX30 index that have complete data in 2016-2020.. Variables that affect the capital structure used are profitability, liquidity, and asset structure. In this study, there were 12 populations. The data analysis technique in this study used and two-stage regression. The results find that Profitability, Liquidity and Assets Structure are the determinant of Capital Structure. Capital structure obtained from the first stage of regression has a negative and significant effect on Firm Value.